From 4ps to 4es: Drivers of Phygital Purchase Intention in Generations Y and Z - Djohan Gunawan; Y. Johny Natu Prihanto; Purnamaningsih Purnamaningsih (Ilomata International Journal of Management, 2026)
Introduction: At the start of 2024, Indonesia’s 185 million internet users and 139 million social media users formed a highly connected landscape where this research explores how the marketing mix’s evolution (from 4Ps to 4Cs to 4Es) associates with purchase intentions across Generation Y and Z in a phygital environment. Methods: Utilizing a quantitative approach, data from 372 valid Indonesian respondents were gathered via non-probability accidental sampling using a 4-point Likert scale. PLS-SEM was employed to analyse direct and total effects within the conceptual model. Results: The structural path analysis confirms that the marketing mix successfully evolves from the 4Ps, through the 4Cs, to the 4Es for both cohorts, identifying two distinct behavioural archetypes based on total effects. Generation Y operates as "Pragmatic Converters," whose purchase intent is significantly associated with the Place–Convenience–Everyplace pathway (Original Sample = 0.16, T Statistic = 3.32, and P Values = 0.00), prioritizing immediate accessibility and seamless utility. Conversely, Generation Z acts as "Sceptical Advocates," whose purchase intent is strongly tied to the Product–Customer–Experience pathway (Original Sample = 0.12, T Statistic = 2.32, and P Values = 0.02), requiring deep product validation and high-value, shareable experiences to overcome baseline marketing scepticism. Conclusion: Generation Y values frictionless utility, whereas Generation Z demands transparency and social currency. Consequently, businesses need cohort-specific strategies, maximizing convenience for Generation Y while delivering experience-driven content for Generation Z. The Pragmatic Converter and Skeptical Advocate archetypes provide a strategic roadmap for localized, experience-centric marketing.